Touristification and Conflicts of Interest in Cruise Destinations: The Case of Main Cultural Tourism Cities on the Spanish Mediterranean Coast - Chamizo Nieto, Francisco José; Nebot Gómez de Salazar, Nuria; Rosa-Jiménez, Carlos; Reyes-Corredera, Sergio Jesús (MDPI, 2023)
Tourist demands and the ensuing commodification of habitability in cities have led to the emergence of resistance movements. This study aims to define patterns in touristified cities by measuring the presence of citizen initiatives, together with tourism intensification and related socio-demographic variables. All the indicators have been tested in the Mediterranean port cities of Barcelona and Malaga as they lead the cultural offer. Both municipalities have been analysed at census-section level and show a common urban pattern: the Airbnb offer has spread out in the old town in direct competition with traditional accommodation and replacing long-term rentals. Statistical analysis reveals a significant correlation among citizen initiatives with tourism services, which are the driver mechanisms behind the movements. Cluster maps show a clear centre-periphery pattern according to the tourism intensification set with high coefficient values for tourist accommodation. Bivariate spatial autocorrelation indicates that protest movements emerge in tourism specialisation areas with a high concentration of tourist facilities. Monitoring the proposed indicator system over time may serve as a basis for local administrations to promote new urban policies dealing with overtourism. Future research may redefine and include new variables, test other tourist destinations and consider a smaller non-administrative territorial unit of analysis.
Keywords: Gentrificación; Tourism Intesification; Gentrification; Tourism gentrification; Urban tourism; Overtourism; Indicator system